Essay Genre in Tatar Journalism - Guseinova, Aigul A.; Zayni, Rezeda L. (Journal of History Culture and Art Research, 2017)
In this article, an essay is considered as a journalistic genre in the context of modern Tatar journalism. Using the example of works by contemporary authors in the Tatar-speaking periodicals of Russia, the main genre and the semantic features of this genre are studied. An essay is a publicistic form to reflect on the topical issues of Russian reality. The reproduction of a fact is not so important for an essay. An important role is played by the description of the author’s impressions, reflections and emotions. The periodical press has many materials in the Tatar language in which the author’s opinion, author’s principle and subjective opinion are strongly expressed. In fact, during the last decades of the twentieth century and the beginning of the twenty-first century there was a surge of essays in modern journalism. Due to some political events in Russia during the early 90s of the twentieth century, it was possible to express their thoughts and speak on the urgent problems in society openly in comparison with the Soviet reality. The object of research is essayism as a kind of journalistic creativity, the subject of the study is the essay genre in Tatar journalism. The empirical basis of the work consisted of the essays from Tatar journalists, publicists and writers. Provided that the personality of an author is one of the effectiveness factors concerning the publications in the genre of essay, the essayization of texts in Tatar journalism will be increased in the future.